Сборник задач по ядерной физике: учебное пособие для вузов - Скачков С. В. Сергей Владимирович; Константинов Л. В. Леонард Васильевич; Строганова Р. П. Римма Петровна; Юрова Л. Н. Лидия Николаевна; Топоркова Э. П. Элеонора Петровна (Москва, Физматгиз, 1963)
Авт. указаны перед заглавием